Multipolar Intuitionistic Fuzzy Ideal in B-Algebras - Amigo, Royyan; Hidayat, Noor; Krisnawati, Vira Hari (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
In this paper, we study with the definition of B-algebras, commutative B-algebras and fuzzy ideal in B-algebras. We consider the terminology of multipolar intuitionistic fuzzy ideal. We propose about multipolar intuitionistic fuzzy ideal in B-algebras and some related properties. Then, we discuss about theorems and propositions which contain some conditions for a multipolar intuitionistic fuzzy set become a multipolar intuitionistic fuzzy ideal in B-algebras.